SCALY DERMATOSES TREATMENT AND DIAGNOSIS - Ravshanova D.T. (PEDAGOGS, 2024)
Annotation: The problem of treating lichen planus is still relevant today. An important task of topical application of medicinal compositions is to create an effective concentration in the focus of inflammation and maintain such a concentration for a long period of time. This study describes a method of treating patients with lichen planus with the inclusion of sesoran ointment in standard therapy. A clinical study showed that when using the above drug, the regeneration of lichen planus was observed by the beginning of 2 weeks. The inclusion of sesoran ointment in the treatment regimen makes it possible to accelerate epithelialization and tissue repair, stabilize the inflammatory process.